1991
DOI: 10.1016/1010-7940(91)90217-8
|View full text |Cite
|
Sign up to set email alerts
|

Entrapping of the clotted intra-aortic ballon in the descending aorta

Abstract: Percutaneous insertion of a catheter for intra-aortic balloon pumping (IABP) was introduced in 1979 by Bregman and Casarella and has become a popular technique. Rupture of the balloon, allowing clot to form inside it, is rare. When the clot is large, it may cause entrapping of the balloon. This is a potentially dangerous complication of IABP. We are aware of only one case report of this complication, by Aru and co-workers. The entrapping of the balloon in their report occurred at the site of insertion in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…We noticed evidence of balloon rupture by leakage of blood from the balloon which formed a hardened clot that was not easy to detect clinically. Shafei et al 9 and Lambert 10 reported that balloon rupture and leakage occurred in up to 15.4% of cases. 9 , 10 Tears can be attributed to design and manufacturing issues, insertion technique, and the atherosclerotic nature of the arteries into which an IABP is introduced.…”
Section: Discussionmentioning
confidence: 99%
“…We noticed evidence of balloon rupture by leakage of blood from the balloon which formed a hardened clot that was not easy to detect clinically. Shafei et al 9 and Lambert 10 reported that balloon rupture and leakage occurred in up to 15.4% of cases. 9 , 10 Tears can be attributed to design and manufacturing issues, insertion technique, and the atherosclerotic nature of the arteries into which an IABP is introduced.…”
Section: Discussionmentioning
confidence: 99%
“…The most common complication is limb ischaemia, mainly as a result of thromboembolism. Other major complications are bleeding, arterial injury, infection and paraplegia 5,6 . Entrapment of IABP is extremely rare.…”
Section: Discussionmentioning
confidence: 99%
“…In most reported cases, surgical exploration and arteriotomy have been used for the removal of an entrapped IABP catheter 5–7,10 . The iliac arteries can be exposed either intraperitoneally or extraperitoneally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Occasionally, when a rupture is due to a leak with progressive loss in deflation‐inflation efficiency and a great delay in removal, blood can enter the balloon causing device entrapment ( 21). The tested device of this study, which is coated outside, is not intended to prevent these rare situations because inside coating is unlikely to prevent the clotting of a substantial amount of blood trapped in the balloon.…”
Section: Discussionmentioning
confidence: 99%